Problems of Internally Displaced Children (IDC) in West Ketapang, Madura - Lestari Basoeki S; Endang Warsiki; Fatirnah Haniman; Didik Aryono; Sutjipto (Faculty of Psychology, Universitas Surabaya, 2004)
-